TRANSMISI BUDAYA ISLAM ARAB SAUDI DAN IMPLIKASINYA BAGI PENDIDIKAN ISLAM DI INDONESIA - M. Zainuddin Tsalis; Abdul Quddus (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research explores the transmission of Islamic values ​​from Saudi Arabia to Indonesia and their implementation in Islamic education in Indonesia. This research discusses two key questions: the process of transmitting Islamic culture from Saudi Arabia and the impact of this cultural transmission on the Islamic education system in Indonesia. This research uses a qualitative approach, using interviews with educational figures and documentation analysis to collect comprehensive data. Research findings reveal that cultural transmission occurred historically through trade, scholars, and the influence of educational institutions such as the Islamic University of Medina. Additionally, modern technology and media facilitate cultural exchange today. The transmission has led to significant changes in the Indonesian education curriculum, teaching methods, and the integration of Arabic language education. However, challenges remain in balancing Saudi cultural influences while preserving unique local Indonesian values. This research contributes to understanding how Islamic education in Indonesia can develop to become more contextual and culturally integrated, effectively balancing global and local influences.